Co-pretreatment of Municipal Wastewater and Landfill Leachate by Chemical Coagulation Using Ferric Chloride and Aluminum Sulfate - Tunc, Muslun Sara (Gazi Univ, 2020)
In this study, co-pretreatment of municipal wastewater (MW) and landfill leachate (LL) was investigated by means of coagulation using ferric chloride and aluminum sulfate. The effects of operating conditions on process performance were examined, which included pH, coagulant type and coagulant dose. For both coagulants, the best removal efficiency was achieved at the initial pH of 5. At this pH, the removal efficiencies of chemical oxygen demand (COD), suspended solids (SS) and turbidity were 82%, %99 and %99, respectively with ferric chloride and 72%, 98% and 98.5%, respectively with aluminum sulfate. For the ratios ranging between 10:1 and 5:1 of MW to LL, the optimum dose was determined as 500 mg/L for both coagulants. When the ratio of MW to LL was reduced from 5:1 to 1:1, the coagulant dose required was raised from 500 to 1000 mg/L and the removal efficiency of pollutants reduced. Better removal efficiencies were achieved by ferric chloride in comparison to aluminum sulfate. The results revealed that coagulation could be applied as pretreatment for co-treatment of MW and LL.
Keywords: Alum; Coagulation; Ferric chloride; Landfill leachate; Municipal wastewater